The effect of different exercise training protocols on MMP-9 and TIMP-1 gene expression in rat myocardium - Mehran Ghahremani; Elham Pourrezaei; Saeed Naghibi; Afshar Jafari (Sport Sciences and Health Research)
Background: There are conflicting findings regarding the effect of various training modalities on the cardiovascular disease mechanisms induced by undesirable modifications in extracellular matrix (ECM) factors such as MMP-9 and TIMP-1.Aim: This study was conducted to investigate the effect of different training protocols on the MMP-9 and TIMP-1 gene expression in the myocardium of Wistar male rats.Materials and Methods: Forty-eight adult Wistar male rats (aged: 8 weeks) were randomly allocated into two control (Con8w/base, n=8; and Con16w/end control, n=8) and four training groups (MICT, n=8; PICT, n=8; HIIT, n=8; and MIST, n=8). The training protocols consisted of 8 weeks (5 days/week) of Moderate-Intensity, Continuous Training (MICT: 37 min running with 65% vVO2max), Moderate-Intensity, Swimming Training (MIST: 30 min free-swimming), Progressive-Intensity, Continuous Training (PICT: 28 min running with a progressive increase in the incline of the treadmill by 2% per week), and High-Intensity Interval Training (HIIT: four running bouts 4 min with 90 to 100% vVO2max + 3 min with 50-65% vVO2max). Myocardial samples were isolated 24 hours after the last training session. Gene expression was determined using the real-time PCR method. All data (M±SD) were analyzed by one-way ANOVA and Tukey's post-hoc tests at α ≤0.05.Results: There were significant differences between MMP-9 and TIMP-1 expression in the animals myocardium after different exercise training protocols (P<0.01). The lowest and highest MMP-9/TIMP-1 ratios were in the HIIT and MICT protocols, respectively.Conclusion: According to our findings, the HIIT protocol may play a more influential role in enhancing myocardial ECM-remodeling and fibrosis indicators during lifespan than the other exercise protocols.